Dynamics and diversity in adolescents’ experienced barriers and facilitators for physical activity maintenance - Timothy A. Houtman; Froukje Sleeswijk Visser; Amy van Grieken; Valentijn Visch (PLoS ONE, 2025)
Despite the well-documented health benefits of physical activity (PA), over 80% of adolescents worldwide fail to meet recommended daily levels. This study identified experienced barriers and facilitators for PA maintenance among Dutch adolescents, examine how they form barrier and facilitator profiles, and explore how barriers and facilitators evolve over time. First, we conducted 21 interviews with adolescents (13–16 years) to uncover relevant barriers and facilitators. Then, we developed and applied a card sorting task based on Q methodology, and examined barrier and facilitator configurations with 30 adolescents (aged 13–18 years) who had maintained a physical activity for ≥2 years, followed by interviews. Factor analysis revealed five facilitator profiles: Mental and physical health benefits, A way to be myself around others, Pursuing health goals, Developing confidence and strength, and Developing along my own path. Four barrier profiles emerged: Low motivation and energy, Not a good fit for me, Balancing act, and Proximity, possibility and perception. Facilitator profiles ranged from immediate characteristics of the activity, such as enjoyment, social connection, and mental well being, to more future-oriented drivers such as autonomy and self-development. Barriers profiles varied from predominantly internal (e.g., low motivation) to external (e.g., distance, weather) or mixed influences linking life demands to reduced personal resources. Across participants, enjoyment was the most consistent facilitator, but perceived influences often shifted with time, from immediate, activity-based facilitators related to competence and relatedness, toward motivations tied to autonomy, identity and coping with growing responsibilities characteristic of this life stage. These results highlight the diversity and dynamic nature of barriers and facilitators in adolescent PA maintenance. Tailoring PA promotion programs to adolescents’ evolving motivations and constraints can increase their effectiveness, supporting sustained active lifestyles into adulthood.